(untitled) (Communications in Computational Physics, 2020)
This work is concerned with the modelling of the interaction of fluid flow with flexibly supported rigid bodies. The fluid flow is modelled by Lattice-Boltzmann Method, coupled to a set of ordinary differential equations describing the dynamics of the solid body in terms its elastic and damping properties. The time discretization of the body dynamics is performed via the Time Discontinuous Galerkin Method. Several numerical examples are presented and highlight the robustness and efficiency of the proposed methodology, by means of comparisons with previously published results. The examples show that the present fluid-structure method is able to capture vortex-induced oscillations of flexibly-supported rigid body.